1997
DOI: 10.1007/s002560050193
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous neurilemmoma of the fibula

Abstract: We present a case of intraosseous neurilemmoma of the fibula in a 56-year-old woman. The case showed the typical radiographic appearance except for the presence of spotted calcifications that mimicked a cartilaginous tumor. Enhanced MR images revealed the heterogeneity of the tumor, which consisted of Antoni type A and B tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…14 The x-ray features of intraosseous schwannoma include a well-defined lytic lesion, scelerotic margins, lobulated or trabeculated contour, cortical expansion and erosion, and absence of central calcification. 4,15,16 However, the x-ray findings are nonspecific. 1,6,16 The MRI appearance of the tumor tends to be isointense to skeletal muscles on T1-weighted images and markedly hyperintense to fat on T2-weighted images.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…14 The x-ray features of intraosseous schwannoma include a well-defined lytic lesion, scelerotic margins, lobulated or trabeculated contour, cortical expansion and erosion, and absence of central calcification. 4,15,16 However, the x-ray findings are nonspecific. 1,6,16 The MRI appearance of the tumor tends to be isointense to skeletal muscles on T1-weighted images and markedly hyperintense to fat on T2-weighted images.…”
Section: Discussionmentioning
confidence: 96%
“…4,15,16 However, the x-ray findings are nonspecific. 1,6,16 The MRI appearance of the tumor tends to be isointense to skeletal muscles on T1-weighted images and markedly hyperintense to fat on T2-weighted images. 4,16,17 Although most schwannomas contain both Antoni A and Antoni B arrangements, further subclassification of these lesions by predominate tissue has been considered.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, an intraosseous schwannoma involving a long bone may be associated with the second mechanism, the tumor arises and develops within the nutrient canal, and related to the site of the nutrient artery; however, the most common location of intraosseous schwannomas in long bones remains to be elucidated. A total of 4 cases of intraosseous schwannoma of the fibula were previously reported with clear radiographic figures (4)(5)(6), and 3 of these cases occurred in the diaphysis of the fibula. As free vascularized fibular grafts have been widely used to cover skeletal bone defects larger than 6 cm (16), it has been reported that the nutrient canal into the fibula is positioned between 12 and 18 cm from the tip of the fibula, in the diaphysis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 200 cases have been previously reported; of these cases, the most common sites of the involved bones were the mandible and sacrum (2). Although a number of cases of intraosseous schwannoma involving the long bones have been previously reported (3)(4)(5)(6)(7)(8), this type of disease is relatively rare, and the typical location at which an intraosseous schwannoma of the long bones may arise is uncertain. Intraosseous schwannoma presents as a slowly enlarging and painless mass (8); however, if the bone becomes affected and a microfracture is caused, the mass becomes painful.…”
Section: Introductionmentioning
confidence: 99%
“…Although it can appear in any age, the usual age group is the third or fourth decade.There appears no predilection for sex. 2 They have been reported to arise in mandible 3 (most common), sacrum, 4 lumbar, 5 thoracic 6,7 and cervical vertebrae, 8,9 femur, 10 tibia, 庐 bula, 2 sternum, 11 calcaneum, 12 etc. The reason for the increased incidence in mandible is due to either the long intra-osseous course of the nerve or the increased predilection of schwanomas to the head and neck region, which has a large supply of sensory nerves.…”
Section: Discussionmentioning
confidence: 99%